The Comparison of Bacterial Contamination in Different Stages of Fixed Restoration - F Ehsandost; S Nosouhian; SA Havaei; M Sabouhi (Isfahan University of Medical Sciences, 2008)
Introduction: Cross infection control is of a great concern and great attention should be paid to it.Dentistry offices and laboratories are predisposed to make and transmit contamination; Thereforeboth dentists and laboratory director shall regard cross infection control policies in order toprevent dental cross contamination between patients and personnel. The aim of this research was toasses the quality of bacterial contamination in fixed restoration in different stage of preparation.Methods and materials: In this descriptive analytical study, samples were obtained from 75 crownand bridges in metal frame work. Bisque and glaze stage and microbial cultures were taken.Information's were statistically analyzed by MC Namara Analysis.Results: From 75 samples, 37 (%49.32) were contaminated. Prevalence of pathogenic and nonpathogenic bacteria was as follows: Staphylococcus in 27 cases (%72.97), Bacteriallus 7 in cases(%18.91), Klebsilla in 2 cases (%15.40), and E-coli in 1 case (%2.72). The difference between thisstages was not statistically significant (p value = 0.754).Discussion: Staphylococcus is the most commonly found bacteria in fixed restorations. It may bedue to handling restorations without gloves. According to 49.32% contamination, infection controlin procedures is essential